Pengaruh Komunikasi Persuasif dan Pola Konsumsi Skincare terhadap Penerapan Sustainable Beauty - Gita Juniarti; A Hermila; Rahmat Taufik R. L. Bau; La Ode Gusman Nasiru (Pawarta: Journal of Communication and Da'wah, 2024)
This research tells about several factors that influence the younger generation's interest in implementing sustainable beauty, namely choosing skincare that is safe for living creatures and environmentally friendly. Sustainable Beauty will consider the ingredients contained in skincare to keep it safe for the environment, as well as the packaging of the skincare. The factors in question are persuasive communication and skincare consumption patterns among students in Gorontalo City. The student population in Gorontalo City was chosen because skincare has become essential for them and part of their lifestyle. The number of samples taken reached 97 people, with the criteria being students in Gorontalo City and using skincare in the last month. The data collection technique uses a questionnaire, and the data analysis technique uses multiple regrets. The results show that H1 and H2 are accepted; a relationship exists between persuasive communication and skincare consumption patterns on implementing sustainable beauty. Partially, the relationship between the two is 24.144%. Influential contributions were dominated by the persuasive communication variant, 12.4%, while the skincare consumption pattern variable was 11.744%. Meanwhile, 75.856% of the implementation of sustainable beauty is influenced by other factors. The suggestion from this research is that the community's knowledge, attitudes and behaviour need to be developed to implement sustainable beauty in Gorontalo City. Apart from that, the role of the government in creating and implementing waste policy is also vital. Even in managing the environment, public awareness still needs to improve, so this is the job of every stakeholder in society.